ANALISIS KEBUTUHAN PELATIHAN UNTUK MEMENUHI KOMPETENSI LITERASI INFORMASI PENGELOLA PERPUSTAKAAN SEKOLAH - Johan, Riche Cynthia (Universitas Pendidikan Indonesia, 2012)
Libraries have never escaped from the service provider or business that is often called a librarian or library administrator. For schools, the librarian must be skilled and dedicated in searching, organizing and interpreting information needed by teachers and students. Without a competent librarian, the library can not be operated properly and effectively.Development of information and communication technologies are also pushing the world into a library for technological literacy activities. One school librarian competency standard is competence in using ICT in the library and information science.Competence is defined as a measure to determine the level of librarians in using the knowledge and skills. Competency requirements are constantly changing, so librarians should keep them updated.This study is a preliminary study conducted to determine the training needs of librarians in secondary education. In general, the problems posed in this study is how the competence of the teacher librarian or school library staff? The research question is described as follows: whether the competence of the librarians have been in accordance with government regulations No. 25 of 2008? Furthermore, this study also identify particular type of training that can enhance information literacy competency?The method in this study is survey research methods. A survey research is an approach that is generally used for extensive data collection and more. Through this method are expected to answer the problem by describing the actual number of teachers and librarians that describes the instrumentation to analyze the information literacy competencies already held by the teacher librarians in managing the school library.